2015
DOI: 10.1038/srep15645
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical role of the Kuroshio Current in the amphibious mudskipper Periophthalmus modestus indicated by mitochondrial DNA data

Abstract: Quaternary climatic cycles have influenced marine organisms’ spatial distribution and population dynamics. This study aimed to elucidate the evolutionary influences of contemporary and glacial physical barriers on the population structure, demography and colonization history of the mudskipper (Periophthalmus modestus) based on a mitochondrial gene segment (ND5) from 131 individual fish sampled in the northwestern Pacific Ocean. The current Kuroshio Current and the glacial exposure of the Taiwan Strait appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 106 publications
(111 reference statements)
2
48
0
Order By: Relevance
“…The marginal seas of the South China Sea, the East China Sea, and the Sea of Japan/East Sea may have served as glacial refugia, although intraspecific variation in demographic histories is common across taxa (Ni et al., ). He, Mukai, Chung, and Zhang () found the amphibious mudskipper Periophthalmus modestus colonized northward from the South China Sea through the East China Sea along the coasts of Korea and Japan. Other studies have found higher haplotypic diversity in southern South Korea and southern Japan (i.e., East China Sea) as compared to Honshu and Hokkaido populations (Ho, Kwan, Kim, & Won, ; Kim, Hoarau, & Boo, ), suggesting northward colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marginal seas of the South China Sea, the East China Sea, and the Sea of Japan/East Sea may have served as glacial refugia, although intraspecific variation in demographic histories is common across taxa (Ni et al., ). He, Mukai, Chung, and Zhang () found the amphibious mudskipper Periophthalmus modestus colonized northward from the South China Sea through the East China Sea along the coasts of Korea and Japan. Other studies have found higher haplotypic diversity in southern South Korea and southern Japan (i.e., East China Sea) as compared to Honshu and Hokkaido populations (Ho, Kwan, Kim, & Won, ; Kim, Hoarau, & Boo, ), suggesting northward colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The marginal seas of the South China Sea, the East China Sea, and the Sea of Japan/East Sea may have served as glacial refugia, although intraspecific variation in demographic histories is common across taxa (Ni et al, 2014). He, Mukai, Chung, and Zhang (2015) found (Ho, Kwan, Kim, & Won, 2014;Kim, Hoarau, & Boo, 2012), suggesting northward colonization. However, although studies have found southern clade haplotypes decrease to the north (Azuma & Chiba, 2015), no studies, to our knowledge, have found as sharp a break as observed in our study of Gracilaria vermiculophylla in the NW Pacific (Figure 1, Figure S1).…”
Section: Phylogeographic Structure In the Native Rangementioning
confidence: 99%
“…the barnacle Chthamalus moro ; Wu, Tsang, Chan, & Chu, ). These islands may have served as glacial refugia during the LGM, resulting in distinct speciation events (He, Mukai, Chu, Ma, & Zhang, ). Along the coast of mainland China, the phylogeographic patterns of the rocky shore limpets Cellana toreuma and the Siphonaria species revealed a strong biogeographic break at the mouth of Yangtze River, resulting in the separation of the northern populations of the Yellow Sea from the Southern East China Sea and South China Sea populations (Wang, Tsang, & Dong, ).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on the mudskipper Boleophthalmus pectinirostris , for example, revealed two geographic clades: one clade is distributed along the coasts of China and Taiwan, and the other clade is in South Korea and Japan (Chen, Hong, Chen, Wang, & Zhang, ). Monsoon circulations in the East China Sea may promote gene flow between the East China Sea and South China Sea mudskipper populations (He et al., ). Along the coast of mainland China, in the region around the mouth of the Yangtze River, a division exists between the northern and southern populations of the mitten crab Eriocheir sensu stricto, and the mangrove bivalves Cyclina sinensis and Atrina pectinata (Ni, Li, Kong, & Yu, ).…”
Section: Introductionmentioning
confidence: 99%
“…The marginal seas of South China Sea, the East China Sea and the Sea of Japan/East Sea may have served as glacial refugia, though intraspecific variation in demographic histories are common across taxa (Ni et al 2014). He et al (2015) found the amphibious mudskipper Periophthalmus modestus colonized northward from the South China Sea through the East China Sea along the coasts of Korea and Japan. Other studies have found higher haplotypic diversity in southern South Korea and southern Japan (i.e., East China Sea) as compared to Honshu and Hokkaido populations (Kim et al 2012;Ho et al 2014), suggesting northward colonization.…”
Section: Discussionmentioning
confidence: 99%